Implementation of STEM-oriented learning strategy toward science literacy skills in elementary school students - Listiyana, Asmi; Bima, Muhammad Zidan Arya; Khusna, Nashikhatul; Dewi, Pambayun Wardani Candra; Putri, Shianindra Rahmani; Yuniarti, Yeni; Anantanukulwong, Roseleena; Angoy, Raisalam D.; Sukardi, Rendi Restiana (Education and Development Research, 2023)
The study aims to examine the effect of STEM-oriented learning on science literacy skills in elementary school students. This study employed quasi-experimental research. The study population was all Sekolah Dasar Negeri Mungkid 2 students. The sample of this research was the entire students of Class IV SDN Mungkid 2 which totaled 16 students. The samples were obtained through a purposive sampling technique. The results of data on students' scientific literacy abilities were obtained through pretest and posttest activities. The data were then analyzed using SPSS Statistics 20. Data processing was started with a normality test, paired sample t test, hypothesis test, and N-gain test. The results of this study showed that implementation of STEM-oriented learning has proven to influence of elementary school students’ science literacy skills.